Safety profile of biologic agents for Behçet's disease in a multicenter observational cohort study. (18th August 2015) - Cantarini, Luca; Talarico, Rosaria; Generali, Elena; Emmi, Giacomo; Lopalco, Giuseppe; Costa, Luisa; Silvestri, Elena; Caso, Francesco; Franceschini, Rossella; Cimaz, Rolando; Iannone, Florenzo; Galeazzi, Mauro; et al.
Abstract: Aim: The primary aim of this study was to explore the safety profile of biologic treatments in Behçet's disease (BD), based on their mechanism of action; the secondary aim was to study any potential variation in terms of retention rate according to each single drug. Method: We studied a total of 85 treatment regimens with biologic agents from 64 patients. The total follow‐up was calculated as 8640 patient‐years (anti‐tumor necrosis factor [TNF]‐alpha 7.020, anti‐interleukin [IL]‐beta 1.368). Cumulative rates of drug retention were studied using the Kaplan–Meier plot and covariates in the regression model included the mechanism of action of the biologic agent, other concomitant therapies, disease duration, sex, age at start of drug therapy; for each confounding factor hazard ratios (HR) were calculated. Results: The most frequently prescribed biologic treatments were anti‐TNF‐alpha agents (79%), while anti‐IL1‐beta was used in the remaining regimens. Concomitant disease‐modifying antirheumatic drugs were prescribed in 36% of patients, mainly cyclosporine and methotrexate, while in 35/85 regimens low‐dose glucocorticoids were associated. During the follow‐up, in all but one regimen the safety profile was free of any adverse events or serious adverse events; we observed only one case of endocarditis, reported during the 10th month of etanercept. Conclusion: Data from a large multicenter cohort suggest that anti‐TNF‐alpha and anti‐IL1‐beta agents are characterized by an excellent safety profile in BD.